(untitled) (Bioresearch Communications, 2023)
This study investigated the parasites of three species of croakers (Pennahia anea, Panna microdon, and Johnius argentatus) and their effect on host’s tissues. Fish samples were collected directly from the local fishermen and the fish landing station of Saint Martin’s Island, Bay of Bengal on a regular monthly basis. A total of 448 individuals of parasites were collected of which nine species of parasites were identified including three crustaceans, four nematodes, one pentastomida, and one acanthocephala. The nematode Procamallanus longus had the highest prevalence (50%) and intensity (10.33) compared with the other parasites. The prevalence and intensity of parasites were slightly higher in female fish (55%, 35) than in male fish (50%, 20). The stomach and liver were the most favorable infection sites (53.33%). Furthermore, parasites with the largest length and weight showed the highest prevalence and intensity (66.66% and 38.4 as well as 80% and 72.5, respectively). In histopathological investigations, the most important alterations in various tissues of fish were hemorrhage, necrosis, fatty droplets, edema, vacuolar degenerations, missing villi, haemosiderotic nodules, ovarian follicle disruption, and parasitic cell distribution. Bioresearch Commu. 9(2): 1297-1304, 2023 (July)